MODEL BISNIS, PENCIPTAAN NILAI DAN PENGUNGKAPAN MODAL INTELEKTUAL - Totok Dewayanto (STIE Pelita Nusantara Semarang, 2019)
Whenever a business enterprise is established, it employs a particular business model that describes the design or architecture of the value creation, delivery, and capture mechanisms it employs. The essence of a business model is in defining the manner by which the enterprise delivers value to customers, entices customers to pay for value, and converts those payments to profit. It thus reflects management’s hypothesis about what customers want, how they want it, and how the enterprise can organize to best meet those needs, get paid for doing so, and make a profit. There is currently signiﬁcant debate worldwide regarding business reporting. The concept of the ‘business model’ has entered into the discourse, as has the concept of ‘integrated reporting’, adding to the established debate regarding accounting for intangible assets and, more generally, intellectual capital (IC). The purpose of this article is to understand the influence of business model on intellectual capital disclosure.